Pendampingan Psikologis pada Ibu yang Mengalami Baby Blues Akibat Tuntutan Sosial dalam Budaya Patriarki di Suradadi Timur Kota Mataram: (Psychological Accompanying for Mothers Experienced with Baby Blues Due to Social Demands in Patriarchal Culture in East Suradadi of Mataram City) - Herlina Fitriana; Lalu Abdurrachman Wahid Rahman; Masruri; M. Wahyullah; Pujiarohman (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Baby blues is an unstable condition that occurs in post-natal mothers that affects a person's physical and psychological state. This situation occurs usually because of a lack of social support from the surrounding environment. The purpose of this service is to create a society that is more concerned with the psychological and spiritual state of religion in postpartum mothers. This method of community service user a Participatory Action Research (PAR) approach. This assistance is carried out on 12 couples (husband and wife) who have children aged 2-4 months. Based on a series of mentoring events from beginning to end, the service team got several important points that became interesting findings in this service and became notes and evaluation materials. First, the theme in this service is something that has just been heard in the community, many of the service participants experience the baby blues but they ignore it because it is considered not a serious thing even though if it is not handled immediately it will lead to more severe things such as suicide or killing a baby or prolonged depression. Second, the implementation of psychological assistance should be carried out in the form of individual counseling because what participants need is individual counseling so that they can share experiences more deeply.